Direct purchases of U.S. Treasury securities by Federal Reserve Banks - Kenneth D. Garbade (Federal Reserve Bank of New York, 2014)
Until 1935, Federal Reserve Banks from time to time purchased short-term securities directly from the United States Treasury to facilitate Treasury cash management operations. The authority to undertake such purchases provided a robust safety net that ensured Treasury could meet its obligations even in the event of an unforeseen depletion of its cash balances. Congress prohibited direct purchases in 1935, but subsequently provided a limited wartime exemption in 1942. The exemption was renewed from time to time following the conclusion of the war but ultimately was allowed to expire in 1981. This paper addresses three questions: 1) Why did Congress prohibit direct purchases in 1935 after they had been utilized without incident for eighteen years, 2) why did Congress provide a limited exemption in 1942 instead of simply removing the prohibition, and 3) why did Congress allow the exemption to expire in 1981?
Keywords: E58; H62; H63; 330; treasury debt issuance; Federal Reserve; direct purchases